DESAIN LEMBAR KERJA PESERTA DIDIK UNTUK PEMBELAJARAN BIOLOGI DI SMA DARI HASIL RISET EKSPERIMENTAL - Hati, Pini Permata; Wulandari, Sri; L.N. Firdaus, L.N. Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Teaching materials for biology learning in Senior High Schools that utilize local potential are still less varied. This study aims to produce Student Worksheets (LKPD) utilizing the results of experimental research on vegetative propagation of Jambu Kristal (Psidium guajava L.) which is currently increasingly popular and highly economic value. To achieve this goal, two methods have been used, namely experimental research to obtain knowledge content for LKPD design innovations, and partially development research (R & D) methods for designing of the LKPD (Analysis and Design stage). The first stage uses a completely randomized design with five treatment concentrations [%]: 0; 25; 50; 75; 100 of red onion tuber extracts (Allium cepa L.) given to P. guajava graft growth medium, each with 3 replications was applied in this study. After 6 weeks of experimentation, data from variance analysis showed that the treatment concentration of 25% gave the best results for the number and length of roots. These results can then be used as material and basis for the preparation of the LKPD for the Subject of Vegetative Growth in Class XII High School Biology Learning through the Scientific Approach 2013 Curriculum. For use on a broader scale, these LKPD’s must be tested for feasibility and limited use testing.Keywords: Allium cepa L., Biology Learning, Learner Worksheets, Psidium guajava L. Grafting, Senior High School, Vegetative Root Growth.